Directional associations between memory impairment and depressive symptoms: data from a longitudinal sample and meta-analysis. Issue 10 (8th November 2017) - Yu, Junhong; Lim, Hui-Ying; Abdullah, Fadzillah Nur d/o Mohd; Chan, Hui-Minn; Mahendran, Rathi; Ho, Roger; Kua, Ee-Heok; Power, Michael John; Feng, Lei
Abstract: Background: Previous cross-lagged studies on depression and memory impairment among the elderly have revealed conflicting findings relating to the direction of influence between depression and memory impairment. The current study aims to clarify this direction of influence by examining the cross-lagged relationships between memory impairment and depression in an Asian sample of elderly community dwellers, as well as synthesizing previous relevant cross-lagged findings via a meta-analysis. Methods: A total of 160 participants ( M age = 68.14, s.d. = 5.34) were assessed across two time points (average of 1.9 years apart) on measures of memory and depressive symptoms. The data were then fitted to a structural equation model to examine two cross-lagged effects (i.e. depressive symptoms→memory; memory→depressive symptoms). A total of 14 effect-sizes for each of the two cross-lagged directions were extracted from six studies (including the present; total N = 8324). These effects were then meta-analyzed using a three-level mixed effects model. Results: In the current sample, lower memory ability at baseline was associated with worse depressive symptoms levels at follow-up, after controlling for baseline depressive symptoms. However, the reverse effect was not significant; baseline depressive symptoms did not predict subsequent memory ability after controlling for baseline memory. The results of the meta-analysis revealed the same pattern of relationship between memory and depressive symptoms. Conclusions: These results provide robust evidence that the relationship between memory impairment and depressive symptoms is unidirectional; memory impairment predicts subsequent depressive symptoms but not vice-versa. The implications of these findings are discussed